Peran Pendidikan Kristen dalam Memerangi Kekerasan pada Anak (Violance Against Child) - Andreas Fernando; Yonatan Alex Arifianto; Sumiyati Sumiyati (Sekolah Tinggi Teologi Tenggarong, 2021)
Many children have experienced violence both in closed spaces and in open spaces and nowadays this incident can be a frightening specter for children if the violence is recorded in the digital world. Child abuse is a serious problem for the whole family. Because often found child abuse occurs in the family and close people. This article written using descriptive qualitative research methods with a literature study approach. So, it can be concluded that the role of Christian education in combating the behavior and impact of violence against children, firstly: providing understanding to Christians about the nature of violence against children. Second, with this understanding, it was found that the role of Christian education in preventing and overcoming violence against children from a biblical perspective can be applied. Then the third is to provide education for parents the importance of taking care of and nurturing children in a good and right attitude. And have an attitude of rejecting violence against children regardless of the arguments and forms.AbstrakBanyak anak mengalami kekerasan baik di ruang tertutup maupun di ruang terbuka dan saat ini kejadian itu bisa menjadi momok menakutkan bagi anak bila kekerasan tersebut terekam di dunia digital. Kekerasan anak adalah persoalan serius bagi seluruh keluarga. Sebab sering ditemukan kekerasan anak terjadi dalam keluarga dan orang terdekat. Artikel ini ditulis menggunakan metode penelitian kualitatif deskritif dengan pendekatan studi pustaka. Maka, dapat disimpulkan bahwa peran pendidikan Kristen dalam memerangi perilaku dan dampak kekerasan terhadap anak, pertama: memberikan pengertian kepada orang Kristen tentang hakikat kekerasan terhadap anak. Kedua, dengan adanya pengertian tersebut didapat adanya peran pendidikan Kristen dalam mencegah dan menanggulangi kekerasan terhadap anak dalam perspektif Alkitab dapat diterapkan. Kemudian ketiga memberikan edukasi bagi orangtua pentingnya menjaga dan memelihara anak dalam sikap yang baik dan benar. Serta memiliki sikap menolak terhadap kekerasan terhadap anak apapun dalil dan bentuknya.